Late-onset opportunistic infections while receiving anti-retroviral therapy in Latin America: burden and risk factors. (September 2022) - Núñez, Isaac; Crabtree-Ramirez, Brenda; Shepherd, Bryan E.; Sterling, Timothy R.; Cahn, Pedro; Veloso, Valdiléa G.; Cortes, Claudia P; Padgett, Denis; Gotuzzo, Eduardo; Sierra-Madero, Juan; McGowan, Catherine C.; Person, Anna K.; et al.
Highlights: Late opportunistic infections in HIV have not been properly characterized. Around 8% of more than 10, 000 patients had late-onset opportunistic infections. Most common infections were tuberculosis, esophageal candidiasis, and Pneumocystis jirovecii ( P. jirovecii ). Higher CD4 cell count and undetectable viral load were associated with lower risk. Treatment switch and prior history of AIDS were associated with higher risk. Abstract: Objectives: The aim of this study was to describe the incidence, clinical characteristics, and risk factors of late-onset opportunistic infections (LOI) in people who live with HIV (PWLHA) within the Caribbean, Central and South America network for HIV epidemiology. Methods: We performed a retrospective cohort study including treatment-naive PWLHA enrolled at seven sites (Argentina, Brazil, Chile, Peru, Mexico, and two sites in Honduras). Follow-up began at 6 months after treatment started. Outcomes were LOI, loss to follow-up, and death. We used a Cox proportional hazards model and a competing risks model to evaluate risk factors. Results: A total of 10, 583 patients were included. Median follow up was at 5.4 years. LOI occurred in 895 (8.4%) patients. Median time to opportunistic infection was 2.1 years. The most common infections were tuberculosis (39%), esophageal candidiasis (10%), and Pneumocystis jirovecii ( P. jirovecii ) pneumonia (10%). Death occurred in 576 (5.4%) patients, and 3021 (28.5%) patients were lost to follow-up. A protease inhibitor–based regimen (hazard ratio 1.25), AIDS-defining events during the first 6 months of antiretroviral-treatment (hazard ratio 2.12), starting antiretroviral-treatment in earlier years (hazard ratio 1.52 for 2005 vs 2010), and treatment switch (hazard ratio 1.31) were associated with a higher risk of LOI. Conclusion: LOI occurred in nearly one in 10 patients. People with risk factors could benefit from closer follow-up.